DEVELOPMENT OF PATHOLOGICAL CHANGES IN THE ORAL CAVITY ORGANS OF ANIMALS UNDER CONDITIONS OF POLYNEUROPATHIES OF DIFFERENT GENESIS - K. V. Tykhonovych; А. А. Kotvytska; S. M. Beregovyi; К. S. Neporada (Проблеми екології та медицини)
The aim of our research is to study the effect of polyneuropathy of different genesis on the development of pathological changes in the large salivary glands and periodontal tissues of animals. Methods. The study was conducted on 62 laboratory rats of both sexes. Toxic polyneuropathy was induced by paclitaxel injection, experimental type 1 diabetes mellitus was modeled by streptozocin injection, and alcoholic polyneuropathy was induced by chronic administration of increasing concentrations of ethanol. The development of polyneuropathy was confirmed by a change in the the pain sensitivity threshold (PST) using the Randall-Selitto tensoalgometric method. In the homogenate of oral cavity organs, total proteolytic and total antitryptic activity, catalase activity, content of TBARS, average mass molecules, oxidatively modified proteins, fucose and glycosaminoglycans (GAG), and amylase activity were determined. The level of total, protein-bound and non-protein sulfhydryl groups, activity of superoxide dismutase, glutathione peroxidase, glutathione transferase, glutathione reductase; content of reduced and oxidized glutathione, diene conjugates and Schiff bases were determined in blood serum. Results. We established the increasing of PST in animals that were simulated neuropathies of different genesis. All three types of polyneuropathies are accompanied by the development of carbonyl-oxidative stress in the soft tissues of the periodontium and large salivary glands of rats, which is evidenced by a probable increase in the content of oxidatively modified proteins and the content of TBARS, as well as average mass molecules compared to these indicators in intact animals . Under the conditions of modeling all three polyneuropathies, the protein-synthetic activity in the large salivary glands is suppressed, as evidenced by a decrease in the activity of α-amylase. Under conditions of experimental diabetic and toxic neuropathy in the salivary glands of animals, changes in the proteinase-inhibitor balance of the compensatory type are observed. We found that polyneuropathies of different genesis cause increased catabolism of biopolymers of the extracellular matrix of the periodontal connective tissue of rats, which confirms the increase in the content of GAG and fucose compared to these indicators in control animals. Conclusions. Under conditions of diabetic, toxic and alcoholic neuropathy, the amylolytic activity of the large salivary glands of animals is suppressed, the balance of the pro- and antioxidant system changes. When modeling peripheral polyneuropathy in animals by administration of paclitaxel, streptozocin, and ethanol, the development of periodontal syndrome is observed, the leading pathogenetic mechanisms of which are increased catabolism of connective tissue glycoconjugates and the development of oxidative stress and proteinase-inhibitor imbalance.